Pengaruh Financial Distress, Ukuran Perusahaan, dan Leverage Terhadap Manajemen Laba dengan Kepemilikan Manajerial Sebagai Variabel Moderasi pada Perusahaan Sektor Ritel yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Puspita, Eka; Ruwanti, Gemi; Asyikin, Jumirin; Boedi, Soelistijono (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to examine the effect of financial distress, firm size, and leverage on earnings management with managerial ownership as a moderating variable in retail companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research employs a quantitative approach using secondary data from annual reports and financial statements, with samples selected through purposive sampling, resulting in 57 observations from 43 companies. Data were analyzed using multiple linear regression and moderated regression analysis (MRA) with SPSS 25. The findings reveal that financial distress and leverage have no significant effect on earnings management, while firm size shows a significant positive influence on earnings management. Furthermore, managerial ownership does not moderate the relationship between financial distress, firm size, and leverage with earnings management. These results indicate that firm size plays a dominant role in driving earnings management practices, while relatively small managerial ownership has not been sufficient to act as an effective control mechanism. Therefore, companies are advised to maintain transparency in financial reporting, and investors are encouraged to consider firm size and ownership structure when assessing earnings quality.